Co-operative financial institutions and local development in China. Issue 1 (June 2015) - Loubere, Nicholas; Zhang, Heather Xiaoquan
Highlights: We examine the trajectory of China's co-operative financial landscapes. We outline how co-operative finance has been de-localised and commercialised. This has altered the role financial co-operatives play in local development. We explore the re-emergence of rural co-operative finance since 2007. We provide evidence of complexity and heterogeneity of informal co-operatives. Abstract: In recent decades the Chinese financial system has undergone dramatic restructuring, which has substantially altered the country's mutual and co-operative financial institutions. This paper aims to contribute to our understanding of the process, practice and consequences of these developments by systematically charting the trajectory and dynamics of the co-operative financial landscape in China, and by analysing the role that these financial institutions have played in China's socioeconomic change. It is argued that China's financial co-operatives have been de-localised through processes of consolidation and centralisation. They have also been increasingly commercialised within a system based on 'market logic', which has changed their developmental role in the Chinese economy. At the same time, however, recent policy has sought to reinstitute locally-focused financial and farmer co-operatives in rural areas. Moreover, local informal and semi-formal modes of co-operative organisation and action have continued to be widespread across the country.